Phylogenetic analysis of the complete mitochondrial genome of the white peacock butterfly Anartia jatrophae saturata (Insecta: Lepidoptera: Nymphalidae) - Payment, Josephine E. (Mitochondrial DNA B Resour, 2020)
The white peacock butterfly Anartia jatrophae saturata Staudinger, 1884 (Nymphalidae: Nymphalinae: Victorini), lives in the neotropics. Genome skimming with Illumina sequencing of A. jatrophae saturata allowed the assembly of a complete circular mitogenome of 15,297 bp, consisting of 81.4% AT nucleotides, 22 tRNAs, 13 protein-coding genes, two rRNAs, and a control region. Anartia jatrophae COX1 features an atypical start codon (CGA); ATP6, COX1, ND1, ND4, ND4L, ND5, and ND6 exhibit incomplete stop codons completed in the mRNA by the addition of 3′ A residues. Contrary to previous phylogenetic hypotheses, phylogenetic reconstruction places A. jatrophae as sister to nymphalid tribe Nymphalini.